Incidence and characterization of pressure injuries in Covid 19 patients, Hospital Nacional Hipólito Unanue, Lima 2022 - Martínez Véliz , Marivel Rosa (2023)
Peru is immersed in the problem of Covid 19, it is currently facing the fifth wave due to the variants and persistence of SARS CoV 2; The research work was carried out in the third wave 2022, caused by the omicron. Objetives: To determine the incidence and characterization of pressure injuries in Covid 19 patients at the Hospital Nacional Hipólito Unanue Lima 2022. Material and Methods: Basic research, descriptive level, population it was made up of all the patients who were treated in the ICU1 and ICU2 of the Hospital under study, the observation sheet was used as the technique, the instrument was the observation sheet. Results: The incidence of pressure injuries was 54.5%, the age is from 50 to 59 years with 27.3%, the male sex with 68.2%, the time to develop the pressure injuries greater than 72 hours with 43, 2%, without a vaccination record 25%, very high risk level 61.3%, having prone position as risk factors 17.5%, most frequent location of pressure injuries in the sacrum with 27.5%, with a category of II degree in 50%, the number of pressure injuries that the patients presented was one with 83.3%. Conclusions: The incidence was 54.5%, predominantly male, the age range is 50 to 59 years, the most frequent location was the sacrum, the category of II degree pressure injuries and the number of lesions per pressure is one per patient.